(untitled) (Global Journal of Science Frontier Research, 2017)
The study assessed rural women’s involvement in agriculture in Okpo District, Kogi State, Nigeria. Data were collected from 120 randomly selected rural women farmers using a structured questionnaire. Data were analyzed using frequencies, percentages and mean scores. Results of the study showed that cassava (80%), groundnut (75%), vegetables (62.5%), cowpea (60%), maize (57.5%) and bambaranut (56.7%) constituted predominant crops grown by the respondents while poultry (63.3%), goats (70.8%) and sheep (41.7%) were the major livestock reared. Findings also indicated high involvement of farmers in land clearing (91.6%), weeding (90.9%), sowing/planting (88.4%), harvesting (87.5%), transportation of produce/products (85.8%), processing (77.3%), marketing (79.2%) and storage (67.5%). Major constraints to participation in agriculture included limited access to land (M = 2.26), lack of access to credit (M = 2.15), limited time for agricultural activities (M = 2.07), lack of access to inputs (improved seeds, fertilizers, agro- chemicals) (M= 2.05), lack of modern storage facilities (M = 2.03) and lack of access to appropriate agricultural technologies (M = 2.00). The study concluded that rural women farmers in the study area were small-scale producers who grew subsistence food crops, kept poultry and small ruminants and contributed about 68-92% of their labour in all agricultural operations. However, they were constrained by lack/limited access to agricultural productive resources, hence low production and productivity. In the light of the foregoing, it is recommended that rural women farmers be provided with improved varieties of crops they cultivate while efforts are made to introduce to them more valued crops that would enhance their production. Also, access to relevant agricultural productive resources and timely information as well as gender-sensitive technologies that would reduce drudgery in farming operations, processing and storage activities could free them time to